VEGF dose regulates vascular stabilization through Semaphorin3A and the Neuropilin‐1+ monocyte/TGF‐β1 paracrine axis. Issue 10 (7th September 2015) - Groppa, Elena; Brkic, Sime; Bovo, Emmanuela; Reginato, Silvia; Sacchi, Veronica; Di Maggio, Nunzia; Muraro, Manuele G; Calabrese, Diego; Heberer, Michael; Gianni‐Barrera, Roberto; Banfi, Andrea
Abstract VEGF is widely investigated for therapeutic angiogenesis, but while short‐term delivery is desirable for safety, it is insufficient for new vessel persistence, jeopardizing efficacy. Here, we investigated whether and how VEGF dose regulates nascent vessel stabilization, to identify novel therapeutic targets. Monoclonal populations of transduced myoblasts were used to homogeneously express specific VEGF doses in SCID mouse muscles. VEGF was abrogated after 10 and 17 days by Aflibercept treatment. Vascular stabilization was fastest with low VEGF, but delayed or prevented by higher doses, without affecting pericyte coverage. Rather, VEGF dose‐dependently inhibited endothelial Semaphorin3A expression, thereby impairing recruitment of Neuropilin‐1‐expressing monocytes (NEM), TGF‐β1 production and endothelial SMAD2/3 activation. TGF‐β1 further initiated a feedback loop stimulating endothelial Semaphorin3A expression, thereby amplifying the stabilizing signals. Blocking experiments showed that NEM recruitment required endogenous Semaphorin3A and that TGF‐β1 was necessary to start the Semaphorin3A/NEM axis. Conversely, Semaphorin3A treatment promoted NEM recruitment and vessel stabilization despite high VEGF doses or transient adenoviral delivery. Therefore, VEGF inhibits the endothelial Semaphorin3A/NEM/TGF‐β1 paracrine axis and Semaphorin3A treatment accelerates stabilization of VEGF‐induced angiogenesis.